PENINGKATAN KETERAMPILAN BERPIKIR KRITIS PEMBELAJARAN MEMBACA PEMAHAMAN MELALUI MODEL PROBLEM BASED LEARNING (PBL), KOMBINASI THINK PAIR SHARE (TPS) DAN TALKING STICK DI KELAS IV SDN SUNGAI MIAI 4 BANJARMASIN - Imelda Rosiana; Mahmuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study seeks to enhance critical thinking and reading comprehension skills in students by implementing the Problem-Based Learning (PBL) paradigm in conjunction with Think Pair Share (TPS) and Talking Stick methodologies. The issue encountered is the inadequate critical thinking and reading comprehension abilities of fourth-grade pupils at SDN Sungai Miai 4 Banjarmasin, attributable to traditional and less engaging instructional methods. This research employed a Classroom Action Research (CAR) methodology executed across four cycles, with 19 students as participants. The data gathering methods comprised the observation of instructor and student activities, critical thinking skill assessments, and evaluations of learning outcomes. The results demonstrate that the regular implementation of the three learning models enhances the quality of learning. Teacher and student activities demonstrated a considerable enhancement from the "adequate" category to the "very good" category. The students' critical thinking skills improved from 21% to 100%. Learning achievement increased from 21% in the initial cycle to 100% in the fourth cycle. This enhancement demonstrates that the PBL paradigm, in conjunction with TPS and Talking Stick, is beneficial in fostering critical thinking skills and reading comprehension in elementary school pupils. This study advocates for the adoption of this learning model as a novel approach to improve the quality of Indonesian language education at the primary level.